Assessment of The Difficulty of Mathematics High-Level Reasoning Using Focus Group Discussion and Program Item Approaches - Rukli Rukli; Ma'rup Ma'rup (Universitas Negeri Makassar, 2021)
This study aims to estimate the difficulty level of high-level reasoning math problems by comparing the estimated difficulty level of the Focus Group Discussion (FGD) approach and the Iteman program. The estimation of the FGD approach uses a semantic differential scale on a scale of 1-7, while the Iteman program uses version 4.0. The study used a quantitative-comparative approach involving 79 FGDs of students and teachers of SMP/MTs in Soppeng Regency. Each FGD consisted of four people, one teacher and three students of class VIII. The comparative of difficulty level using Scheffe test with a significance level of 0.05. The results showed that the average level of difficulty in the FGD approach had significant similarity with the average level of difficulty in the output of the Iteman program approach. This means that the estimated level of difficulty of the FGD examinees has a similarity with the output of the Iteman program from the response data of the FGD examinees. This shows that examinees from FGD in assessing the level of difficulty of high-level reasoning questions can be the teacher’s choice in schools other than the Iteman program.